The Effectiveness of Lactobacillus plantarum Administration in Patients with Atopic Dermatitis - Izzati, Ismatu Aghni Fatwa; Pramuningtyas, Ratih; Bestari, Rochmadina Suci; Nurhayani, Nurhayani (Universitas Muhammadiyah Semarang, 2022)
Background: Atopic dermatitis is a chronic and residual inflammatory skin disease with increased prevalence in every year. The medications that are often given can cause serious side effects if it given in the long-term. The treatment of Lactobacillus plantarum is expected to be safer long-term treatment option for patient with atopic dermatitis.Objective: The objective is to determine the effectiveness treatment of Lactobacillus plantarum in patients with atopic dermatitis.Method: The research design was a Systematic Review with a qualitative approach using meta-synthesis analysis type. The search was conducted on 3 databases: PubMed, Science Direct, and Google Scholar. Result: Total articles obtained were 239 with 16 duplicate data. 211 articles were included in the exclusion criteria and 5 articles were interventions with combination probiotics. So there are 7 articles included in the research with clinical trials, open trials, pilot studies, and 4 research using the randomized controlled trial Double Blind design. All results showed improvement in symptoms with the SCORAD index or Skindex-16. Several studies also measured IgE, IL-4, IL-10, IL-13, IL-17, the percentage of Th1, Th2, Treg, TGF-β, IFN-γ and obtained different results. Conclusion: Treatment of Lactobacillus plantarum in patients with atopic dermatitis is effective to reducing symptoms and as an immunomodulator.